Development of Professional Identity in Journalism Students Using Liberal Education Methods - N. S. Avdonina (Высшее образование в России)
In the conditions of robotization and automation of journalistic activities, journalists need to develop professional competencies that will allow them to perform the tasks of complex individual and collective creative activity, namely, authoring and editing. A modern journalist is primarily an author, a creator of meanings and values, and only then a relay of information. Changes in working conditions and the profession affect the understanding of oneself, a specialist has to rediscover the image of himself in the profession and the image of the profession itself, which is the core of professional identity. Modern universities are looking for innovative models of training journalists. One of such innovative educational systems can be so called liberal education. In Russian universities, journalism education according to the principles of the liberal education system is organized at the RANEPA, Novosibirsk State University, Tyumen State University, NArFU named after M.V. Lomonosov. However, there is a lack of research on the topic of the effectiveness of liberal education in the context of the formation of professional identity. The article discusses the results of using methodologies from the liberal education system to develop professional identity at the university for students in the direction 42.03.02 “Journalism” in the disciplines “Introduction to World Journalism”, “History of Foreign Journalism”, “History of Foreign Journalism: XX Century” and “International Journalism”. The goal was the introduction of liberal education techniques, namely, analytical writing, in-depth, slow reading and joint work on media projects, which contribute to the formation of professional identity of future journalists who are ready to work in the new conditions of a digital society. The author analyzes her own experience in using the above methods. As the main research method, a content analysis of student activity products is used.